Post‐operative renal function following nephrectomy as part of en bloc resection of retroperitoneal sarcoma (RPS). Issue 1 (14th July 2015) - Hull, Melissa A.; Niemierko, Andrzej; Haynes, Alex B.; Jacobson, Alex; Chen, Yen‐Lin; DeLaney, Thomas F.; Mullen, John T.
<x xml:space="preserve">Abstract</x> Background and Objectives Although resection of RPS with en bloc nephrectomy confers the potential benefit of improved locoregional tumor control, little has been published about the long‐term post‐operative renal function of these patients. Methods Retrospective review of 54 patients undergoing nephrectomy for RPS was performed. Clinicopathologic and treatment characteristics, pre‐ and post‐operative creatinine (Cr) values, and estimated glomerular filtration rates (eGFR) were recorded. The primary outcome measure was progression of chronic kidney disease (CKD) stage. Results Median preoperative eGFR was 85 ml/min. Post‐nephrectomy, median nadir eGFR was 44 ml/min, rebounding to 62 ml/min at median follow‐up of 50 months. Of 49 patients with preoperative eGFR ≥60 ml/min (CKD stage 1, 2), 51% preserved eGFR ≥60 postoperatively, whereas 49% progressed to CKD stage 3 (eGFR 30–59). Independent risk factors for progression of CKD stage were age and preoperative eGFR. Eleven patients died of recurrent disease, whereas no patient died of end stage renal disease (ESRD) or required dialysis. Conclusions Although progression of CKD stage occurs in nearly one‐half of patients followed for more than 4 years after nephrectomy for RPS, no patient progressed to ESRD or had a limitation in systemic therapy options, even with progression to CKD stage 3. J. Surg. Oncol. 2015 111:98–102. © 2015 Wiley Periodicals, Inc.